Hukum Perusahaan Analisis Peran dan Tanggung Jawab Notaris Dalam Pendaftaran Akta Dan Pengesahan Badan Hukum pada Penggunaan Layanan Ditjen Ahu Online - Yasyari, Andi Muhammad Faizal; Septya, Annisa Cahya; Sari, Wulan (Syntax Literate, 2025)
In accordance with the Decree of the Minister of Justice and Human Rights Number M-05 HT.01.01 Year 2002, all legal entity settlements including the legalization of Limited Liability Company (PT) deed establishment, approval of amendments to Articles of Association, registration of fiduciary guarantees, and registration of wills must be conducted through the Online Legal Entity Administration System (Sistem Administrasi Badan Hukum or SABH). Consequently, the Notary is granted the exclusive authority to register these legal acts digitally. This research employs a normative juridical method, utilizing statutory and conceptual approaches, to analyze the Notary's role and responsibility in the registration of deeds and legalization of legal entities via the Directorate General of AHU Online services. The findings indicate that the Notary's role is critical, involving the input and comprehensive verification of deed data to prevent entry errors. Furthermore, the Notary bears the full responsibility for any errors originating from their office, requiring the Notary to carry out and bear the cost of all corrections, albeit still requiring cooperation from the applicant regarding the necessary data.